2005
DOI: 10.1109/tnsre.2005.847373
|View full text |Cite
|
Sign up to set email alerts
|

Repeated voltage biasing improves unit recordings by reducing resistive tissue impedances

Abstract: Reactive tissue encapsulation of chronically implanted microelectrode probes can preclude long-term recording of extracellular action potentials. We investigated an intervention strategy for functionally encapsulated microelectrode sites. This method, known as "rejuvenation," involved applying a +1.5 V dc bias to an iridium site for 4 s. Previous studies have demonstrated that rejuvenation resulted in higher signal-to-noise ratios (SNRs) by decreasing noise levels, and reduced 1-kHz site impedances by decreasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 25 publications
5
124
1
1
Order By: Relevance
“…This effect only occurred in vivo, as they were unable to duplicate these results with an electrode in a saline bath. These results could be explained by work from Johnson et al (Johnson et al, 2005) who found that the most substantial and consistent impedance change came from protein adsorption and the cellular layers surrounding the electrode. In turn, stimulation through a given contact can modify the tissue microstructure of the local encapsulation, increasing conductivity and decreasing electrode impedance.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This effect only occurred in vivo, as they were unable to duplicate these results with an electrode in a saline bath. These results could be explained by work from Johnson et al (Johnson et al, 2005) who found that the most substantial and consistent impedance change came from protein adsorption and the cellular layers surrounding the electrode. In turn, stimulation through a given contact can modify the tissue microstructure of the local encapsulation, increasing conductivity and decreasing electrode impedance.…”
Section: Discussionmentioning
confidence: 89%
“…Encapsulation is the final stage of the foreign body reaction, wherein the body attempts to destroy or isolate any non-native substance. The tissue response includes both an early antiinflammatory response due to insertion trauma and a sustained response induced in part by the interplay among micromotion, tethering, and device biocompatibility (Johnson et al, 2005). Prior studies have indicated that encapsulation thickness around the DBS electrode lead is at least 25 ÎŒm and no greater than 1 mm (Haberler et al, 2000;Hemm et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These requirements would seem to suggest the use of a single microelectrode as a reference, instead of an unmatched larger electrode. Unfortunately, because of the small size of a microelectrode, coupled with fibrous encapsulation endemic to long-term cortical implants (Edell et al 1992;Johnson et al 2005;Ludwig et al 2006;Polikov et al 2005;Schmidt et al 1993;Szarowski et al 2003;Turner et al 1999;Vetter et al 2004;Williams et al 1999;Xindong et al 1999), the impedance of a microelectrode reference adds significant uncorrelated thermal noise to cortical recordings (Kovacs 1994;Schmidt and Humphrey 1990;Shoham and Nagarajan 2003;Webster 1998). Moreover, the microelectrode reference could potentially register neural signal as well as uncorrelated biological noise-adding both to neural recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, several different approaches have been proposed, including chemical and physical modification of the surface sensing area [50,54], scaling of the sensor size to make the implant less invasive [55], development of more soft, flexible and conformable materials [27,56] and implementation of a rejuvenation protocol to prolong the implant life time [57,58].…”
Section: Long Term Stabilitymentioning
confidence: 99%